Efektivitas Pengeluaran Publik dan Kebijakan Pajak terhadap Pertumbuhan Ekonomi di Negara Berkembang - Adelia Marta Lubis; Gracelino Prasetyo Nainggolan; Fredysyah Putra; Ariel Muhammad Jadhi Sembiring (Universitas 45 Surabaya, 2025)
Public spending and taxation policies are essential fiscal tools that significantly contribute to economic growth, especially in developing nations. This study aims to assess the effectiveness of governmental expenditures and tax policies in promoting sustainable economic development. Employing a quantitative methodology through panel data regression analysis, this study investigates the connection between public expenditure, tax policies, and economic progress across multiple developing countries. Secondary data were gathere.